Działalność inwestycyjna przedsiębiorstw a efektywnościowe strategie inwestycyjne - Siewiera, Agnieszka (Company's Investment Activity and Efficient Investment Strategies, 2007)
A company's market position and changes occurring in the socio-economic environment shape the investment activity of a company. In great part it also depends on company's ability to fulfill its potential. Investments play a very important role in company's development and are the best method of increasing company's market value. Because the effects of project's realization are spread over long period of time and are often irreversible, the investment project has to meet not any the needs of environment, but also has to be compliant with company's strategy. Central coordination of project'si and exploitation in the aspect of company's strategic aim, is a main condition of success. Investment project's strategy forms a base to conduct essential analyses concerning the supply and tad, the customer's behaviour, the market rivals, and the company's socio-economic and political environment. From the economic point of view, any investment that guarantees the attainment of planned results can be accepted for realization. However, the basic aim of long-term planning is to ¡lieve an optimal combination of all the economic and technical elements, such as: production increase, cost reduction, technological efficiency and profit increase. Only the proper combination of is elements, together with possibly low risk factor, guarantees company's success.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 367-375